Development of Siangan Village as a Tourism Village Towards Sustainable Community-Based Tourism in Gianyar Regency - I Putu Gede Satria Wiraharja; I Wayan Chandra Adyatma; I Made Dwi Sumba Wirawan (Universitas Warmadewa, 2025)
Siangan Village is one of the villages in Gianyar Regency. Siangan Village consists of 6 Traditional Villages and 11 Banjar Dinas (the smallest of local government in Bali below the village). Siangan Village is a village that has high economic potential compared to other villages in Gianyar District. Currently, Siangan Village is realizing Siangan as a Tourism Village, and is trying to explore the existing potential to be developed as a spiritual tourism village. The people of Siangan Village are quite active in arts activities by utilizing the